The Representation of Slavery of the Characters in the Beautiful Novel is Luka by Eka Kurniawan - Vidya Vidya; Desma Yuliadi Saputra; Diana Romdhoningsih (CV. Edujavare Publishing, 2026)
The issue of slavery is still one of the serious problems that reflects the dark side of social life in Indonesia. This phenomenon still continues to take root from the colonial to postcolonial periods. This research aims to represent the slavery of the characters in the novel Cantik itu Luka by Eka Kurniawan using the perspective of Spivak's subaltern. The research uses a qualitative descriptive method with reading and recording techniques. The results of the study show that there are 15 data that represent physical, economic, and sexual slavery. The three forms of slavery show the loss of agency, freedom, and voice of the characters in the novel Cantik itu Luka by Eka Kurniawan due to hegemonic or colonial power relations. The results of the analysis using Spivak's subaltern perspective, it can be concluded that the novel Cantik itu Luka by Eka Kurniawan represents 15 data on slavery practices that cross the Dutch colonial era, Japanese occupation, and post-independence.